2018
DOI: 10.3389/fpls.2018.00287
|View full text |Cite
|
Sign up to set email alerts
|

Can Elevated Air [CO2] Conditions Mitigate the Predicted Warming Impact on the Quality of Coffee Bean?

Abstract: Climate changes, mostly related to high temperature, are predicted to have major negative impacts on coffee crop yield and bean quality. Recent studies revealed that elevated air [CO2] mitigates the impact of heat on leaf physiology. However, the extent of the interaction between elevated air [CO2] and heat on coffee bean quality was never addressed. In this study, the single and combined impacts of enhanced [CO2] and temperature in beans of Coffea arabica cv. Icatu were evaluated. Plants were grown at 380 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 78 publications
2
67
0
4
Order By: Relevance
“…The impacts of supra-optimal temperatures on coffee bean quality traits reported by Ramalho et al (2018) were lower than what are commonly observed in the field. Nevertheless, prevalence of high temperatures in the field often coincides with decreased water availability and high atmospheric VPD (compared to the controlled conditions in the study of Ramalho et al (2018)).…”
Section: Coffee Bean Qualitymentioning
confidence: 56%
See 4 more Smart Citations
“…The impacts of supra-optimal temperatures on coffee bean quality traits reported by Ramalho et al (2018) were lower than what are commonly observed in the field. Nevertheless, prevalence of high temperatures in the field often coincides with decreased water availability and high atmospheric VPD (compared to the controlled conditions in the study of Ramalho et al (2018)).…”
Section: Coffee Bean Qualitymentioning
confidence: 56%
“…The impacts of supra-optimal temperatures on coffee bean quality traits reported by Ramalho et al (2018) were lower than what are commonly observed in the field. Nevertheless, prevalence of high temperatures in the field often coincides with decreased water availability and high atmospheric VPD (compared to the controlled conditions in the study of Ramalho et al (2018)). Given that water supply per se might affect coffee bean quality (Vinecky et al 2017), it is anticipated that a negative interaction between water supply and temperature could occur under field conditions, which would ultimately exacerbate impairments on coffee bean and beverage quality.…”
Section: Coffee Bean Qualitymentioning
confidence: 56%
See 3 more Smart Citations